Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan (Studi pada Perusahaan manufaktur Sektor Industri Dasar dan Kimia yang terdaftar di ISSI Bursa Efek Indonesia Periode 2022): The Effect of Financial Performance on Firm ValueCompanies Studies on manufacturing companies in the Basic Industry and Chemical Sector listed on the Indonesian Stock Exchange ISSI Period 2022 - M. Mustaqim (Universitas Nahdlatul Ulama Sidoarjo, 2023)
This study has the objectives of 1) To determine the effect of partial financial performance by ROA, ROE And EPS on company value by PER. 2) To determine the effect of simultane financial performance by ROA, ROE AND EPS on company value by PER in Basic Industrial and Chemical manufacturing companies listed on the ISSI IDX in 2022. Sampling In this study using a purposive sampling technique and using regression analysis multiple linear in the analyzing data. The results showed that partially or simultaneously the projected financial performance with ROA, ROE and EPS has a significant positive effect on company value projected with PER.